Tindak Tutur Direktif Ibu Rumah Tangga Nelayan kepada Anaknya di Kelurahan Gates Nan XX Kecamatan Lubuk Begalung Kota Padang - Firdaus, Yosi Jannatul; Juita, Novia; Tressyalina, Tressyalina (Universitas Negeri Padang, 2012)
The purpose of this study were to (1) describe type to act directive speeches, converse strategy, increase suavity in acts housewife directive speech fisherman to its child at Gates sub-district Nan XX Lubuk Bagaluang district Padang City,Â (2) describe child response to act mother directive speeches it. Data in observational it is act housewife directive speech fisherman and its child response at Gates sub-district Nan XX Lubuk Bagaluang district Padang City. Data source in observational it is mother discourse and family child response fisherman at Gates sub-district Nan XX Lubuk Bagaluang district Padang City. Gathered data by use of method learns and recording and tech tech note as tech of sequel. Observational finding as follows. First, type acts tending directive speech is utilized is act directive speech see dammed hell first. Both of, tending converse strategy is utilized is frank converse strategy without platitude. Third, act mothers directive speech fisherman family to its child tend decent. Fourth, child response to act mother directive speech it tends positive.